2004
DOI: 10.1088/0960-1317/14/4/025
|View full text |Cite
|
Sign up to set email alerts
|

Wafer bonding using microwave heating of parylene intermediate layers

Abstract: This paper describes a novel wafer bonding technique using microwave heating of parylene intermediate layers. The bonding is achieved by parylene deposition and thermal lamination using microwave heating. Variable frequency microwave heating provides uniform, selective and rapid heating for parylene intermediate layers. The advantages of this bonding technique include short bonding time, low bonding temperature, relatively high bonding strength, less void generation and low thermal stress. In addition, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 12 publications
2
99
0
1
Order By: Relevance
“…Also, these techniques may not be suitable to achieve structures with large aspect ratios, as the Parylene structure is limited by the photolithographic or mold fabrication processes employed. To address these limitations, some studies have focused on leveraging the thermoplastic nature of Parylene to form 3D structures using a hot embossing process [21], as well as a modified polymer bonding technique [22], for both die level [13,23] and wafer level bonding [22,24] to assemble Parylene structures via bonding of a top open structure and a bottom substrate layer. These processes successfully produced microchannel structures while eliminating the need for a sacrificial material.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these techniques may not be suitable to achieve structures with large aspect ratios, as the Parylene structure is limited by the photolithographic or mold fabrication processes employed. To address these limitations, some studies have focused on leveraging the thermoplastic nature of Parylene to form 3D structures using a hot embossing process [21], as well as a modified polymer bonding technique [22], for both die level [13,23] and wafer level bonding [22,24] to assemble Parylene structures via bonding of a top open structure and a bottom substrate layer. These processes successfully produced microchannel structures while eliminating the need for a sacrificial material.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding takes place by chain inter-diffusion between Parylene layers. This phenomenon was reported in [32,39]. The bonding was tested for shear and leakage and was found that it survived the tests.…”
Section: Parylene As a Wafer Bonding Materialsmentioning
confidence: 52%
“…Parylene microchannels were formed and analyzed as a free standing structure and as a wafer bonding material in [32,39]. Use of Parylene as a diaphragm material is shown in [37,40].…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations